Evaluation of compact heat exchanger technologies for hybrid fuel cell and gas turbine system recuperators - Amin, M. Rahul (Strojniški vestnik, 2005)
Hybridized Carbonate and Solid Oxide fuel cell power plants are currently under investigation to fulfill demands for high efficiency and low emissions.Selection of high performance, compact recuperators is essential forsuch applications. In this paper compact heat exchanger (CHEX) technology applicable to hybrid fuel cell and gas turbine technology has been extensivelyreviewed. Various compact heat exchanger designs pertinent to gas-gas recuperative duties for fuel cell and gas turbine (FCGT) hybrid systems are presented. The type of CHEXs considered in this study includedČ brazed plate-fin, fin-tube, microchannel, primary surface and spiral. Comparison of the candidate designs is performed by rating each exchanger witha set of desired criteria. Based on this rating procedure, two CHEX designs namely, plate-fin and microchannel were chosen for further review. Plain, strip, louver, wavy and semicircular surface geometries were then analyzed with a numerical CHEX sizing procedure ultimately to select the most suitable surface geometry for FCGT systems. The brazed plate-fin CHEX having the louver fin geometry was chosen, where numerical results show that this surface holds the greatest potential for CHEX size and cost reduction.
Keywords: prenosniki toplote; turbine plinske; celice gorilne; celice hibridne; rekuperatorji; matematični modeli; numerične metode